2016
DOI: 10.3109/10641963.2015.1107086
|View full text |Cite
|
Sign up to set email alerts
|

Trends in blood pressure control and medication use during 20 years in a hypertension clinic in Japan

Abstract: Guidelines for the management of hypertension have recommended strict control of blood pressure to help prevent cardiovascular disease. The aim of the present study was to evaluate the current status of blood pressure control and trends over the past two decades. Four hundred patients treated for hypertension at Kyushu University Hospital were included in the present study. Blood pressure levels and prescribed antihypertensive drugs were examined in 2011. The average blood pressure was 129/74 mmHg, and the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Although the mean values did not differ appreciably among age groups, a trend was observed towards prescribing of more antihypertensive drugs with advancing age. A recent study of 400 patients attending a Japanese hypertension clinic reported that the number and classes of prescribed antihypertensive drugs were similar between patients aged <80 years and ≥80 years . In the present study, we observed a trend towards greater use of three or more antihypertensive drugs concomitantly in patients aged ≥75 years compared with their younger counterparts.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although the mean values did not differ appreciably among age groups, a trend was observed towards prescribing of more antihypertensive drugs with advancing age. A recent study of 400 patients attending a Japanese hypertension clinic reported that the number and classes of prescribed antihypertensive drugs were similar between patients aged <80 years and ≥80 years . In the present study, we observed a trend towards greater use of three or more antihypertensive drugs concomitantly in patients aged ≥75 years compared with their younger counterparts.…”
Section: Discussionsupporting
confidence: 61%
“…These were also the two most commonly prescribed antihypertensive drug classes in a large Japanese survey carried out from 2005 to 2011, although that study did not stratify patients by age . An analysis of 400 patients attending a Japanese hypertension clinic also reported that CCB (78%) and ARB (66%) were the most commonly prescribed antihypertensives . In the current study, it was notable that the prescription rate for ARB as monotherapy was relatively low in patients aged ≥75 years (11.0% vs 20.0% for CCB), suggesting that physicians were tailoring their prescribing choices according to patient age.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The prescription rate we observed for diuretics was somewhat higher than that reported in a previous large Japanese claims database study from 2011 (8), likely reflecting differences between the patient populations including a higher proportion of patients with heart disease in the current study. There is also some evidence to suggest that introduction of an FDC drug containing ARB+Diuretic may have increased the diuretic prescription rate at some centers in Japan (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…The prescription rate for DUs was lower than for other antihypertensive classes. This may be explained by concern about electrolyte disturbances 30. DUs block the electroneutral sodium chloride cotransporter to decrease BP, but the reduced cardiac output leads to stimulation of the renin-angiotensin-aldosterone and sympathetic systems in both males and females 31.…”
Section: Discussionmentioning
confidence: 99%